(untitled) (Applied Biological Research, 2016)
Five most consumed legumes by rural and urban households of Punjab (India) were evaluated for total iron, dialyzable iron and in vitro iron bioaccessibility. In vitro iron bioaccessibility varied from 3.07 to 9.72% in rural households and 2.78 to 6.39% in urban households. In rural households, iron bioaccessibility was maximum for white chickpeas (9.72%) followed by whole mungbean + mothbean(8.56%) and dehusked Bengal gram (8.41%). The least bioaccessibility was in Bengal gram (3.07%) followed by dehusked mungbean + dehusked lentil (3.51%). In urban households, iron bioaccessibility was maximum in dehusked Bengal gram (6.39%), followed by white chickpea (4.45%) and kidney bean (4.19%) Least bioaccessibility was in whole mungbean (2.67%) and dehusked mungbean + dehusked lentil (2.78%). The average iron bioaccessibility of legume preparations was higher in rural house holds than in urban households which may be attributed to the variation in food preparation practices.